2012
DOI: 10.1007/s11999-011-2001-0
|View full text |Cite
|
Sign up to set email alerts
|

Is Selective Arthroscopic Revision Beneficial for Treating Recurrent Anterior Shoulder Instability?

Abstract: Level IV, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 2 publications
0
23
0
1
Order By: Relevance
“…18,24,25 Several articles in our review had strict exclusion criteria for their patients, including patients with MDI, posterior instability, large glenoid defects, engaging Hill-Sachs lesions, and full-thickness rotator cuff tears, as well as patients who wished to return to contact sports. [25][26][27][28][29][30][31][32][33] One study had no exclusion criteria, and thus patients with known risk factors, such as glenohumeral bone defects, were operated on. 34 In that study only one of the 17 patients had a dislocation after revision surgery because of an altercation and, eventually, required a Bristow procedure.…”
Section: Discussionmentioning
confidence: 99%
“…18,24,25 Several articles in our review had strict exclusion criteria for their patients, including patients with MDI, posterior instability, large glenoid defects, engaging Hill-Sachs lesions, and full-thickness rotator cuff tears, as well as patients who wished to return to contact sports. [25][26][27][28][29][30][31][32][33] One study had no exclusion criteria, and thus patients with known risk factors, such as glenohumeral bone defects, were operated on. 34 In that study only one of the 17 patients had a dislocation after revision surgery because of an altercation and, eventually, required a Bristow procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Previously reported reasons for redislocation include hyperlaxity, not utilizing enough suture anchors, glenoid bone loss, humeral head defect and return to contact sports [1,2,6,9]. Failure analysis in this series showed that recurrent instability was the result of moderate to severe trauma in 7 of 12 (58.3 %) shoulders.…”
Section: Discussionmentioning
confidence: 68%
“…Neri et al [26] reported a recurrence rate of 27 % (3 of 11) after a mean follow-up duration of 34 months after using a suture anchor repair technique with a high rate of rotator interval closure. Arce et al [2] published their results following arthroscopic revision stabilization in 16 patients with three cases of recurrent shoulder instability. In their study, the three patients who experience redislocation all had two prior surgeries [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Revision arthroscopic Bankart repair has been used in patients without glenoid bone loss: Arce et al 8 reported a series of 16 patients, with a failure rate of 19% (3 of 16). In 2014 Friedman et al 1 conducted a systematic review of outcomes after revision anterior stabilization surgery.…”
Section: Discussionmentioning
confidence: 99%